2011
DOI: 10.1002/lary.22341
|View full text |Cite
|
Sign up to set email alerts
|

Robotic endolaryngeal flexible (Robo‐ELF) scope: A preclinical feasibility study

Abstract: The Robo-ELF is a novel robot to assist in driving a flexible endoscope for surgery of the upper aerodigestive tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
(9 reference statements)
0
11
0
1
Order By: Relevance
“…The da Vinci robot (Intuitive Surgical, Inc., Sunnyvale, CA) has been used extensively in transoral robotic surgery of the oropharynx; however, it has been sparsely used in endonasal surgery . This is because the da Vinci robot (Intuitive Surgical, Inc., Sunnyvale, CA) was primarily designed with opposing arms via widely spaced ports for abdominal and thoracic surgery, which is very different from the coaxial manipulation and entry through the narrow nostril for endonasal surgery . To use the da Vinci robot (Intuitive Surgical, Inc., Sunnyvale, CA) to operate within the nasal cavity would therefore require external incisions, rendering the use of this system relatively invasive.…”
Section: Introductionmentioning
confidence: 99%
“…The da Vinci robot (Intuitive Surgical, Inc., Sunnyvale, CA) has been used extensively in transoral robotic surgery of the oropharynx; however, it has been sparsely used in endonasal surgery . This is because the da Vinci robot (Intuitive Surgical, Inc., Sunnyvale, CA) was primarily designed with opposing arms via widely spaced ports for abdominal and thoracic surgery, which is very different from the coaxial manipulation and entry through the narrow nostril for endonasal surgery . To use the da Vinci robot (Intuitive Surgical, Inc., Sunnyvale, CA) to operate within the nasal cavity would therefore require external incisions, rendering the use of this system relatively invasive.…”
Section: Introductionmentioning
confidence: 99%
“…An initial publication documented ability of the flexible robot to visualize the larynx without suspension laryngoscopy, and a further preclinical study has shown successful epiglottectomies in five cadaver specimens and a vocal cord excision in a single cadaver specimen . Similar robotic systems have been described for manipulation of rigid and flexible endoscopes, though the benefits in each case are limited to robotic control of the endoscope itself rather than any robotically enhanced precision of surgical tools otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…The da Vinci master‐slave type robotic surgical system has been used to demonstrate safe and feasible TORS,27, 28, 34 and evidence of decreased length of hospital stay and morbidity is now also becoming available 12, 16. Based on favorable oncologic and functional outcomes demonstrated in multiple studies12, 16–18, 21, 35, 36 and the increasing incidence of oropharyngeal carcinoma secondary to the HPV epidemic in younger healthier patients, TORS is gaining increasing adoption as a useful surgical technique for these tumors.…”
Section: Discussionmentioning
confidence: 99%